The Relationship of Individual, Psychological and Organizational Factors with Nurses' Hand Hygiene Adherence - Wartini, Wartini; Komariah, Maria; Nurhakim, Furkon (Indonesian Journal of Global Health Research, 2024)
The background of low hand hygiene adherence is a problem where this is important to maintain the quality and safety of patients in hospitals. Individual factors, psychological factors and organizational factors influence adherence with five moments hand hygiene which is still low. The aim of this research was to identify factors related to nurses' adherence in implementing the five moments hand hygiene. The correlational analytical research method with a cross-sectional approach was carried out at RSUD Sumedang at November 2023 with samples of 123 nurses. The questionnaire used was based on Herzbergh's motivation theory and the Manchester Clinical Supervison Scale 26-item (MCSS-26). Univariate analysis with frequency distribution, bivariate test using Chi Square, and multivariate analysis with logistic regression. The results show that there is dominant influencing factors supervision (3.178), attitude (2.921) and knowledge (0.138). The conclusion of this research is that there is a relationship between individual factors, psychological factors and organizational factors on adherence with five moments hand hygiene . The dominant influencing factors are supervision, attitude and knowledge. Suggestions for increasing knowledge through education and training as well as regular feedback, giving rewards to increase motivation. Increased supervision through strengthening the functions of IPCLN and IPCN.